Geospatialization of Spilling Facility From Spdc 2015 Oil Spill Reports of The Niger Delta Region of Nigeria - Moses Dolapo Apata; Diepiriye Chenaboso Okujagu; Francis Thomas Beka (Politeknik Negeri Batam, 2019)
A hundred and thirty two (132) Oil spill Incidents that occurred in year 2015 based on the existing SPDC Oil Spill JIV Reports were studied using GIS. The JIV reports were downloaded and the requisite information was acquired and incorporated into ArcMap10.2 and they were analysed to produce different maps. Result shows that about 18,233.04bbl of Oil was spilled and an area of 1,718,091.88m2 was impacted in year 2015.Pipelines account for 65.15% (86) of the spills, followed by flowlines 14.39% (19), Wellheads 13.63% (18) while others account for the rest. Pipelines are the most sabotaged Production Facility with 73.63 %( 81) of the Sabotage that occurred followed by wellhead13.63 % (15) and, flowline 10 % (11) while other Production Facilities account for the rest. This Study also shows that JIV Reports to an extent are a good and convenient tool for characterising Oil spills and the JIV culture should be encouraged. This study should be carried out on all JIV so that they are put in a Digital Format where they can be easily queried to produce the necessary information as needed.